Establishing the Research Agenda for Increasing the Representation of Women in Engineering and Computing - Buse, Kathleen; Hill, Catherine; Benson, Kathleen (Frontiers in Psychology, 2017)
While there is an extensive body of research on gender equity in engineering and computing, there have been few efforts to glean insight from a dialogue among experts. To encourage collaboration and to develop a shared vision of the future research agenda, a two day convening of 50 scholars who work on the topic of gender in engineering and computing was held at a rural conference center. The structure of the conference and the location allowed for time to reflect, dialogue, and to craft an innovative research agenda aimed at increasing the representation of women in engineering and computing. This paper has been written by the conference organizers and details the ideas and recommendations from the scholars. The result is an innovative, collaborative approach to future research that focuses on identifying effective interventions. The new approach includes the creation of partnerships with stakeholders including businesses, government agencies, non-profits and academic institutions to allow a broader voice in setting research priorities. Researchers recommend incorporating multiple disciplines and methodologies, while expanding the use of data analytics, merging and mining existing databases and creating new datasets. The future research agenda is detailed and includes studies focused on socio-cultural interventions particularly on career choice, within undergraduate and graduate programs, and for women in professional careers. The outcome is a vision for future research that can be shared with researchers, practitioners and other stakeholders that will lead to gender equity in the engineering and computing professions.